Assessing the fiscal-monetary policy mix in the euro area - Krzysztof Bańkowski; Kai Christoffel; Thomas Faria (European Central Bank (ECB), 2021)
This paper attempts to gauge the effects of various fiscal and monetary policy rules on macroeconomic outcomes in the euro area. It consists of two major parts - a historical assessment and an assessment based on an extended scenario until 2030 - and it builds on the ECB-BASE -a semistructural model for the euro area. The historical analysis (until end-2019, `pre-pandemic') demonstrates that a consistently countercyclical fiscal policy could have created a fiscal buffer in good economic times and it would have been able to eliminate a large portion of the second downturn in the euro area. In turn, the post-pandemic simulations until 2030 reveal that certain combinations of policy rules can be particularly powerful in reaching favourable macroeconomic outcomes (i.e. recovering pandemic output losses and bringing inflation close to the ECB target). These consist of expansionary-for-longer fiscal policy, which maintains support for longer than usually prescribed, and lower-for-longer monetary policy, which keeps the rates lower for longer than stipulated by a standard reaction function of a central bank. Moreover, we demonstrate that in the current macroeconomic situation, fiscal and monetary policies reinforce each other and mutually create space for each other. This provides a strong case for coordination of the two policies in this situation.
Keywords: E32; E62; E63; 330; Model simulations; Fiscal rules; Monetary policy rules; Joint analysis of fiscal andmonetary policy